Policy Reforms for Safe Online Access to Alcoholic Beverages in Indonesia - Pingkan Audrine (Center for Indonesian Policy Studies (CIPS), 2021)
Despite low rates of alcohol consumption, the direct sale of alcoholic beverages in Indonesia is highly regulated. Highly restrictive access to recorded alcohol means that consumers tend to turn to cheaper and widely available unrecorded alcohol. The rising trend and importance of the digital economy also means that online sales of alcoholic beverages need informed regulations in place to prevent harm to consumers and reduce illicit alcohol markets. Failing to address the issue adequately would only increase the risk of underage drinking and methanol poisoning to millions of Indonesians. Instead of banning online sales of alcoholic beverages, a specific regulatory framework should be considered. This policy paper presents four key reforms to address the problem of unrecorded alcohol and make legal alcohol safely available online; regulatory reforms, verification of alcohol merchants for digital sales, ID-checking for age verification, and shifting the liability to the merchants of the e-commerce providers or the intermediaries.
Keywords: 330; alcohol beverages; spirit; e-commerce; online access; recorded alcohol; unrecorded alcohol; Contraband; Smuggled alcohol; Counterfeit alcohol; Non-conforming alcohol; Surrogate alcohol; alcoholic beverages; underage drinking; Ministry of Trade; National Agency of Drug and Food Control; Ministry of Health; euromonitor; oplosan; digital economy